2009
DOI: 10.1007/s11113-009-9154-5
|View full text |Cite
|
Sign up to set email alerts
|

Demographics and Consumption Patterns in Urban China

Abstract: China, Consumption patterns, Demographics, Household expenditure,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Three income groups were defined as incomes below 200% of the NPL (low), 200%–399% of the NPL (middle), and 400% of the NPL or more (high) (Holahan & Wang, 2004). Supposing the family household size was 3.0 (Yusuf & Brooks, 2009) with NPL at RMB2300, then low-income was below RMB13,800, middle-income was RMB13,800–RMB27,600, and high income was above RMB27,600 (Zhang & Wang, 2008). …”
Section: Methodsmentioning
confidence: 99%
“…Three income groups were defined as incomes below 200% of the NPL (low), 200%–399% of the NPL (middle), and 400% of the NPL or more (high) (Holahan & Wang, 2004). Supposing the family household size was 3.0 (Yusuf & Brooks, 2009) with NPL at RMB2300, then low-income was below RMB13,800, middle-income was RMB13,800–RMB27,600, and high income was above RMB27,600 (Zhang & Wang, 2008). …”
Section: Methodsmentioning
confidence: 99%
“…: 16–20). This has been shown to differ according to region and demographics (Yusuf and Brooks, ). Wang and Li (), who investigated housing consumption as an example, found that neighbourhood and location‐related attributes have a significant impact on people's housing preferences, followed by attributes such as family income, age, education and occupation.…”
Section: State Market and Society In China's Neoliberal Urbanismmentioning
confidence: 99%
“…This number of migrant workers continues to rise despite recent policies that intend to prevent the growth of China’s urban population. However, this particular market segment has been ignored and much research on Chinese consumers has focused on urban elites, missing an opportunity to problematize existing theories of acculturation and its marketing implications (Davis 2000; Yusuf and Brooks 2010; Zhang 2012; Zhou et al 2010).…”
Section: Migrant Workers As An Emerging Segment In the Chinese Politimentioning
confidence: 99%